Causality of Helicobacter pylori infection on eosinophilic esophagitis and potential pathogenesis: a Mendelian randomization study - Zhu, Zhenghui; Yang, Yanqing; Han, Xu; Peng, Lei; Zhu, Hong (Frontiers in Immunology, 2024)
Background: Observational studies have indicated a possible connection between Helicobacter pylori (H. pylori) infection and eosinophilic esophagitis (EoE), but their causal relationship has yet to be established. To investigate the causal associations between H. pylori infection and EoE, we performed a Mendelian randomization (MR) analysis.Methods: Firstly, we conducted both univariable and multivariable Mendelian randomization (MR) analyses. Furthermore, a two-step MR was carried out to ascertain the potential underlying pathways of these associations, particularly the involvement of inflammatory cytokines. We employed the inverse-variance weighted (IVW) method as the main analysis in our MR study. To enhance the credibility of the results, we also conducted several sensitivity analyses.Results: Our study demonstrated a noteworthy correlation between genetically predicted anti-H. pylori IgG antibody levels and a reduced risk of EoE (OR=0.325, 95% CI=0.165-0.643, P value=0.004, adj p value=0.009). No significant causal associations were detected between other H. pylori antibodies and EoE in our study.When it comes to multivariable MR analysis controlling for education attainment, household income, and deprivation individually, the independent causal impact of anti-H. pylori IgG on EoE persisted. Surprisingly, the two-step MR analysis indicated that inflammatory factors (IL-4, IL-5, IL-13, IL-17, and IFN-γ) did not appear to mediate the protective effect of H. pylori infection against EoE.Findings suggested that among the range of H. pylori-related antibodies, anti-H. pylori IgG antibody is the sole causal factor associated with protection against EoE. Certain inflammatory factors may not be involved in mediating this association.These findings make a significant contribution to advancing our understanding of the pathogenesis of EoE and its evolving etiology.